PEMANFAATAN IKLIM DAN TANAH UNTUK PENENTUAN POLA TANAM PADI GOGO, KETELA POHON DAN KACANG TANAH DI KECAMATAN PLAYEN, WONOSARI DAN PONJONG, KABUPATEN GUNUNGKIDUL - , HANIM FATHMANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purposes of this study are to create a map of land suitability classes to enhance the potential of the land according to the requirement conditions of rice (Oryza sativa), cassava (Manihot esculenta) and groundnut (Arachis hypogaea), and to determine the cropping pattern according to climate data obtained. Location of the research is located at Playen, Ponjong and Wonosari District, Gunungkidul, Yogyakarta. This research was conducted with several stages is the survey phase, land suitability analysis and water balance analysis for cropping recommendation. The results indicated that land suitability classes of rice, cassava and groundnut are S3eh and Neh